Genetic polymorphisms of Plasmodium falciparum isolates from Melka-Werer, North East Ethiopia based on the merozoite surface protein-2 (msp-2) gene as a molecular marker - Hussein Mohammed; Ashenafi Assefa; Melkie Chernet; Yonas Wuletaw; Robert J. Commons (Malaria Journal, 2021)
Abstract Background The characterization of parasite populations circulating in malaria endemic areas is necessary to evaluate the success of ongoing interventions and malaria control strategies. This study was designed to investigate the genetic diversity of Plasmodium falciparum isolates from the semi-arid area in North East Ethiopia, using the highly polymorphic merozoite surface protein-2 (msp2) gene as a molecular marker. Methods Dried blood spot isolates were collected from patients with P. falciparum infection between September 2014 and January 2015 from Melka-Werer, North East Ethiopia. Parasite DNA was extracted and genotyped using allele-specific nested polymerase chain reactions for msp2. Results 52 isolates were collected with msp2 identified in 41 (78.8%) isolates. Allele typing of the msp2 gene detected the 3D7/IC allelic family in 54% and FC27 allelic family in 46%. A total of 14 different msp2 genotypes were detected including 6 belonging to the 3D7/IC family and 8 to the FC27 family. Forty percent of isolates had multiple genotypes and the overall mean multiplicity of infections (MOI) was 1.2 (95%CI 0.96–1.42). The heterozygosity index was 0.50 for the msp2 locus. There was no difference in MOI between age groups. A negative correlation between parasite density and multiplicity of infection was found (p = 0.02). Conclusion Plasmodium falciparum isolates from the semi-arid area of North East Ethiopia are mainly monoclonal with low MOI and limited genetic diversity in the study population.